SISTEM MONITORING PERKEMBANGAN AIR BERSIH DAN POLUSI UDARA BERBASIS WEBSITE DI WILAYAH JAKARTA (PURE-IN) - Naufal Arie Wahyu Priadi; Ulinnuha Latifa (Peneliti.net, 2023)
Natural disasters are disasters caused by natural or earth events or activities, such as earthquakes, tsunamis, volcanic eruptions, and floods, and drought may be included in natural disasters. Drought is a situation where the relationship between the availability of water and needs, such as necessities of life, agriculture, economic activity, and the environment are not in harmony. One reason is climate change due to global warming. The impacts are quite diverse, such as a lack of clean water and air pollution. Pure-In, a website for monitoring air pollution and the development of clean water for the DKI Jakarta area, is expected to be the first prevention for the community in preparation for drought. Pure-In has various features, such as monitoring air pollution, mapping clean water in Jakarta, donations, and articles. The results displayed are sufficient to provide information for ordinary people, can provide how the air condition or air pollution in Jakarta is using parameters, such as NO2, PM10, and CO, and also provide a display that sufficiently explains how the air conditioner is in Jakarta. Features such as the mapping of the city of Jakarta are also working well enough to provide locations that have clean water. The embedded donation feature is also quite different, using the Saweria API, and the article feature as reading material for the public about drought and how to prepare for it.